Enhancing Humanitarian Logistics Through Digital Innovation and Systemic Reform: A Narrative Review in Developing Countries - Kurniawan, Deri Alan (Yayasan Sinergi Kawula Muda, 2025)
The increasing complexity of humanitarian crises has brought renewed attention to the efficiency and adaptability of humanitarian logistics and disaster relief supply chains. This narrative review aims to synthesize recent literature concerning the integration of emerging technologies and multi-stakeholder coordination in enhancing disaster response, with a particular focus on developing countries. Using a structured keyword search across academic databases such as Scopus and Google Scholar, the review includes empirical and conceptual studies addressing pre-disaster planning, warehouse distribution, technological integration, and ethical dimensions. Key findings reveal that systemic obstacles, including bureaucratic inefficiencies, fragmented policies, and institutional misalignment, continue to hinder rapid and effective disaster response. In contrast, technological innovations such as IoT and blockchain, alongside digitalized information systems, improve logistical transparency and inter-agency coordination. The review also emphasizes the importance of ethical decision-making and human resource management in ensuring equitable aid delivery. Models employing simulation, multi-criteria analysis, and robust optimization have demonstrated strong potential in enhancing prepositioning and real-time operations. Despite these advances, gaps persist in empirical validation, grassroots engagement, and long-term impact assessments. These insights offer practical implications for humanitarian agencies and policymakers, including the implementation of real-time digital tracking systems, simplification of inter-agency protocols, and prioritization of volunteer training initiatives to enhance logistical agility. By integrating ethical, technological, and systemic perspectives, humanitarian logistics systems can become more resilient and responsive to future global emergencies.